2009
DOI: 10.1021/es900251n
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Intracellular Polyphosphate Dynamics in Enhanced Biological Phosphorus Removal Process using Raman Microscopy

Abstract: A Raman microscopy method was developed and successfully applied to evaluate the dynamics of intracellular polyphosphate in polyphosphate-accumulating organisms (PAOs) in enhanced biological phosphorus removal (EBPR) processes. Distinctive Raman spectra of polyphosphates allowed for both identification of PAOs and quantification of intracellular polyphosphate during various metabolic phases in a lab-scale EBPR process. Observation of polyphosphate at individual cell level indicated thatthere are distributed st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
86
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(95 citation statements)
references
References 21 publications
(30 reference statements)
6
86
0
Order By: Relevance
“…We hypothesized that Accumulibacter in the acetate reactor channeled large amounts of energy to poly-P formation which eventually "saturated" the cells. Indeed, based on Raman imaging, a recent report shows that poly-P inclusions can occupy as much as 75% of the Accumulibacter cell body (37). This metabolic state of Accumulibacter might in turn have allowed Competibacter to proliferate, as assessed here by two independent methods.…”
mentioning
confidence: 77%
“…We hypothesized that Accumulibacter in the acetate reactor channeled large amounts of energy to poly-P formation which eventually "saturated" the cells. Indeed, based on Raman imaging, a recent report shows that poly-P inclusions can occupy as much as 75% of the Accumulibacter cell body (37). This metabolic state of Accumulibacter might in turn have allowed Competibacter to proliferate, as assessed here by two independent methods.…”
mentioning
confidence: 77%
“…Crane et al [17] identified a complex mixture of amorphous calcium phosphate and disordered OCP-like mineral phases. No evidence for a polyphosphate phase (reported in murine bone forming cells (16)), which is expected to have peaks at 700 and 1180 cm − 1 [ [62], was observed. The mineral aggregates that we observed between bone hemi-cylinders are presumably intra-cellular, and represent the earliest stage of mineralization.…”
Section: Discussionmentioning
confidence: 99%
“…Note that validation of the Raman analysis through comparison and correlation with conventional bulk measurements were demonstrated in our previous studies. 12 −14 The filtered samples through 0.45 μm filter papers were analyzed for Orthophosphate (orthoP, (PO 4 3 ) − ) and acetate (CH 3 COO − ) using DX-120 ion chromatograph (Dionex Benelux, Belgium). All phosphorus fractions were measured according to the standard method (4500-P).…”
Section: Methodsmentioning
confidence: 99%